The survival of pathogenic bacteria and plant growth promoting bacteria during mesophilic anaerobic digestion in full-scale biogas plants - Guangdou Qi (2019)
© 2018 Japanese Society of Animal Science The introduction of biogas plants is a promising way to recycle organic wastes with renewable energy production and reducing greenhouse gas. Application of anaerobic digestate as a fertilizer reduces the consumption of chemical fertilizers. In this study, the survival of pathogenic bacteria and plant growth promoting bacteria (PGPB) in two full-scale biogas plants operated at mesophilic condition were investigated. Feedstock and anaerobic digestate samples were collected from biogas plants and bacteria load in samples were detected using standard dilution plate method. Pathogenic bacteria were reduced to not detected level through mesophilic digestion tank except for Campylobacter. However, it could be reduced by 98.7% through a sterilization tank. Bacillus was detected at 8.00 and 7.81 log 10 CFU/g dry matter in anaerobic digestates, and it was also resistant to sterilization tank. Bacillus spp. is considered to be the safe bacteria that hold remarkable abilities for promoting plant growth. The results showed that treatment at biogas plants is effective to reduce pathogenic bacteria in dairy manure, and sterilization could further reduce the sanitary risks of pathogenic bacteria relating to anaerobic digestate application. Anaerobic digestates could also be utilized as bio-fertilizer as the high load of plant growth promoting bacteria.